Pengaruh Ekuitas Merek dan Atribut Produk terhadap Keputusan Pembelian Konsumen Gula Pasir di Pasar Swalayan Kota Surakarta - Mulyo, Tirto; Rahayu, Endang Siti; Riptanti, Erlyna Wida (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
White sugar is one of the beverage ingredients with the highest amount of consumption in Indonesia. This is based on drinking habits and processed foods that use granulated sugar. The large selection of brands and product attributes offered by the company gives people the option to buy white sugar products they want. Consumers have to make decisions in every purchase of white sugar products. This study aims to find out the characteristics of white sugar consumers in Surakarta City supermarkets, analyze the influence of brand awareness/associations, perception of quality, and brand loyalty to brand equity in white sugar consumers in Surakarta City supermarkets, and analyze the influence of brand equity and product attributes on purchasing decisions in white sugar consumers in Surakarta City supermarkets. This research used descriptive method of analytics with a non-probability sampling method using 150 respondents. The method of data collection using interview method with questionnaire. Data analysis using structural equation modeling (SEM) methods with SmartPLS 3.3.3 software. The results showed that white sugar consumers in Surakarta City supermarkets were dominated by 17-30 years old, female gender, undergraduate education level, income of Rp1,500,001.00-Rp3,000,000.00 per month, family members 4 people, the amount of consumption 1.1-5 kg per month, with the gulaku white sugar brand. A significant variable affecting brand equity in white sugar consumers in Surakarta supermarkets is the perception of quality and brand loyalty. The brand awareness variable does not have a significant influence.